The Influence of Food on the Pharmacokinetics of Amlodipine and Losartan after Single-Dose of its Compound Tablets in Healthy Chinese Subjects - Lv, C.; Wei, C.; Wang, X.; Yao, H.; Li, R.; Wang, B.; Guo, R. (Drug Research, 2014)
We aim to identify the effects of food on the pharmacokinetics (PK) of amlodipine, losartan and losartan’s active metabolite (EXP3174) after oral administration of the Compound Amlodipine Tablets with single dose in healthy Chinese subjects. 12 subjects took the compounds (10 mg/100 mg, amlodipine/losartan) at the conditions of a high-fat breakfast and an overnight fast with a washout period of 14 days. Plasma samples were obtained at scheduled time, and determined by HPLC-MS/MS for the concentrations of amlodipine and HPLC-MS for the concentrations of losartan and EXP3174, respectively. PK parameters were calculated using Software Drug and Statistics (Version 2.0). When tablets were co-administered with food, there was no significant difference of AUC for amlodipine and losartan, but the AUC of EXP3174 was reduced by 19.1%. Meanwhile, the Cmax of amlodipine, losartan and EXP3174 were reduced by 11.4%, 20.0% and 41.4%, and the Tmax of losartan and EXP3174 were 1.3 and 1.8 h longer, respectively. No significant difference was found at t1/2 following food intake. In conclusion, the Compound Amlodipine Tablets, are affected by food administration by reducing the AUC of EXP3174. It is thus suggested that the Compound Amlodipine Tablets should be administered 1 h before or 2 h after meal.
Keywords: food; absorption; amlodipine; losartan; EXP3174; pharmacokinetics